2001
DOI: 10.1006/juec.2000.2205
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Lock-in: Do Falling House Prices Constrain Residential Mobility?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
169
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(178 citation statements)
references
References 32 publications
8
169
1
Order By: Relevance
“…Such housing equity constraints have been shown in previous research to be an impediment to residential mobility (e.g. Genesove and Mayer, 1997;Henley, 1998;Chan, 2001;and Ferreira, Gyourko, and Tracy, 2010). Second, couples may be averse to selling their homes when prices are declining if they exhibit loss aversion (Kahneman and Tversky, 1979).…”
Section: B Predicted Effects Of House-price Changes On Divorcementioning
confidence: 87%
See 1 more Smart Citation
“…Such housing equity constraints have been shown in previous research to be an impediment to residential mobility (e.g. Genesove and Mayer, 1997;Henley, 1998;Chan, 2001;and Ferreira, Gyourko, and Tracy, 2010). Second, couples may be averse to selling their homes when prices are declining if they exhibit loss aversion (Kahneman and Tversky, 1979).…”
Section: B Predicted Effects Of House-price Changes On Divorcementioning
confidence: 87%
“…Empirical evidence in support of nominal loss aversion restricting residential mobility includes Chan (2001), Genesove and Mayer (2001), and Engelhardt (2003). Third, empirical evidence (e.g.…”
Section: B Predicted Effects Of House-price Changes On Divorcementioning
confidence: 99%
“…While housing prices clearly matter for moves in both cases, we are primarily interested in their effect on migration at the scale of metropolitan areas, counties, and states. Intra-area studies that examine effects of housing prices on household location decisions include Chan (2001), So et al (2001), Engelhardt (2003), Seig et al (2004), andFerreira et al (2010). 2 Chen and Rosenthal (2008) construct area-level quality of life indices that reflect wages and housing prices.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies conducted prior to the Great Recession typically found housing market declines reduced geographic mobility (Quigley 1987;Stein 1995;Henley 1998;Mayer 1997, 2001;Chan 2001;and Engelhardt 2003). However, much of that earlier research was restricted in terms of the geographic area studied (for example, New York City), the temporal horizon for moving (for instance, an eightyear time horizon), or the demographic group that was affected (for example, younger households).…”
Section: Earnings (See Congressional Budget Office 2007; Van Horn Andmentioning
confidence: 99%